2019
DOI: 10.3390/genes10020119
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression Network Analysis and Hub Gene Selection for High-Quality Fiber in Upland Cotton (Gossypium hirsutum) Using RNA Sequencing Analysis

Abstract: Upland cotton (Gossypium hirsutum) is grown for its elite fiber. Understanding differential gene expression patterns during fiber development will help to identify genes associated with fiber quality. In this study, we used two recombinant inbred lines (RILs) differing in fiber quality derived from an intra-hirsutum population to explore expression profiling differences and identify genes associated with high-quality fiber or specific fiber-development stages using RNA sequencing. Overall, 72/27, 1137/1584, 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 69 publications
(83 reference statements)
0
38
0
Order By: Relevance
“…For WGCNA analysis, K ME values indicated the eigengene connectivity based on the assumption that hub genes are identified by sorted K ME values [33]. In this study, several genes with the highest K ME values in each module were selected as hub genes.…”
Section: Resultsmentioning
confidence: 99%
“…For WGCNA analysis, K ME values indicated the eigengene connectivity based on the assumption that hub genes are identified by sorted K ME values [33]. In this study, several genes with the highest K ME values in each module were selected as hub genes.…”
Section: Resultsmentioning
confidence: 99%
“…Two upland cotton genotypes 69307 with longer and stronger cotton fiber and 69362 with short and weaker cotton fiber were cultivated under standard field conditions (10 rows, each 8 m long and 0.8 m) in Zhengzhou, China [32,33]. Cotton fibers at 5, 10, 15, 20, 25, and 30 days post anthesis (DPA) were collected from bolls for extraction of RNA.…”
Section: Methodsmentioning
confidence: 99%
“…TFs were obtained from P2TF (Predicted Prokaryotic Transcription Factors) database that contains 372,877 TFs from 1,987 prokaryotes [20]. TFs are ranked based on the correlation of TFs with module hub gene [34][35][36]. The TFs thus obtained in these modules were further confirmed for the presence of DNA binding and other regulatory domain using Conserved Domain Database (CDD) [37].…”
Section: Identification Of Stress Responsive Module and Transcriptionmentioning
confidence: 99%
“…It has been previously reported that TFs which are highly correlated with hub gene could be the potential regulators of respective module [34][35][36]. The regulation of darkgreen module PLOS ONE appears to be complex as it possesses multiple TFs.…”
Section: Identification Of Important Regulators and Validation Of Thementioning
confidence: 99%